MESIN PRESENSI CEPAT DENGAN MENGGUNAKAQR CODE DAN WEBCAM - Eka Ardhianto (Universitas PGRI Semarang, 2016)
QR Code is an abbreviation of Quick Response Code. QR Code has been developedby Denso Corporation since 1994 that was first used as an identifier vehicle manufacturingsection. Along with the development needs, QR Code replaces the use of Bar Code in someareas due QR Code can be read only with digital cameras and even webcam and cameraphone.In addition to the use of QR Code as one document security device and QR Code is one of thefast recognition method. So in this study the author tries to take advantage of the QR Code asfast reading and recording of student attendance. The one of the reasons is that the presence ofstudents in each meeting is becoming one of the points of assessment, and the use of digitalcameras have become widespread in many ways, digital camera also embedded built in everylaptop which used by teachers, lecturers and instructors so that presence can be easily done byutilizing the integrated webcam in lapotop.The results of this study is, the application which can utilize QR Code image as the presencecard of students that can be read and recorded using teacher’s, lecturer’s or instructor’slaptop webcams so the process of recording attendance done easily and directly uploaded onacademic information systems